2002
DOI: 10.1590/s0004-282x2002000400004
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous chlorpromazine in the acute treatment of episodic tension-type headache: a randomized, placebo controlled, double-blind study

Abstract: -Acute headache is a very frequent symptom, responsible for a significant percentage of caseload at primary care units and emergency rooms. Chlorpromazine is easily available in such settings. The aim of this study is to conduct a randomized, placebo-controlled, double-blind study to assess the efficacy of chlorpromazine on the acute treatment of episodic tension-type headache. We randomized 30 patients to receive placebo (10 ml of saline intravenous injections) and 30 patients to receive 0.1 mg/Kg chlorpromaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…GTBA en sık rastlanan baş ağrısı tipidir ve hayat boyu prevalansı %8 olarak bildirilmiştir (13). Çalışmamızda GTBA, diğer tip baş ağrılarına göre daha sıktı.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…GTBA en sık rastlanan baş ağrısı tipidir ve hayat boyu prevalansı %8 olarak bildirilmiştir (13). Çalışmamızda GTBA, diğer tip baş ağrılarına göre daha sıktı.…”
Section: Discussionunclassified
“…Klorpromazinin epizodik GTBA'da etkinliğinin yüksek olduğunu bildirilmiştir. Bu çalışma dopaminin baş ağrısı üzerindeki önemini indirekt yoldan göstermesi açısından önemlidir (13 Güçlü bir adrenerjik antogonistir, seratonerjik ve histaminerjik reseptörlere etki eder. Klorpromazinin özellikle antidopaminerjik etkisi migren ve GTBA'daki etkisini açıklayabilir.…”
Section: Discussionunclassified
“…These authors reported an NNT of two versus placebo for achieving a pain free state by 60 minutes. 2 Cicek et.al. randomized 140 patients with acute tension-type headache to receive either metoclopramide 10 mg IV alone, metoclopramide 10 mg IV + pethidine (meperidine) 50 mg IM, pethidine 50 mg IM alone, or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…1 . Several studies have also demonstrated efficacy of parenteral dopaminergic antagonists such as chlorpromazine 2 and metoclopramide 3 for these headaches. Comparative efficacy studies of the dopamine antagonists versus the non-steroidals have yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…The intravenous administration of dipyrone (1000 mg) [120,121] and chlorpromazine (0.1 mg/kg) [122], and the intramuscular form of ketorolac (60 mg) [117] have also proved to be effective for the acute treatment of TTH.…”
Section: Acute Pharmacological Treatmentmentioning
confidence: 99%